Motivasi Kang Jalal Menekuni Pemikiran Sufistik - Muhammad Muhammad (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2021)
Abstract. Jalaluddin Rakhmat (Kang Jalal) is a bachelor's degree in communication science, a graduate of Pajajaran University (Unpad), Bandung, and a master of science in communication research from State University, Ames, Iowa, and a doctorate in political science, a graduate of the Australian National University in Australia(Rahmat, Bridging, p. 144). Jalal is a brilliant Muslim scholar and intellectual, he can speak across disciplines, not only in communication and political sciences, but he can engage in various disciplines of Islam in detail and depth, even his uniqueness gained recognition from Muslim intellectuals and scholars in Indonesia. As a Muslim, Jalal was very interested in studying various Islamic sciences, including Sufism.  Keywords: Kang  Jalal's Motivation, Sufistic Thinking.